Environmental governance in the revitalization of urban streams in Recife - Pernambuco - Brazil (Research, Society and Development, 2021)
The lack of planning of cities in Brazil caused urban sprawl to occur in a disorderly manner, inhabiting the banks of rivers and streams. Due to poor sanitation, the sewage ends up being released in natura into the water bodies, as well as solid waste will stop inside. The channeling of the streams is observed in the city of Recife, wich has 98 strems that flow to seven concentration basins and sub-basins. This research aimed to analyze the process of environmental governance in the revitalization of urban streams in the city of Recife in Pernambuco. A qualitative research was conducted, with interviews with stakeholders. Community leaders report that the channels of communication with the municipal authorities are not efficient and that they only know about the works in their communities at the beginning of them, without participating in decision making. This reflects environmental governance in the revitalization process. In this process, there are indications of the use of governance principles, such as: transparency, subsidiatity, belonging and accountability. There was greater difficulty and incipience in the principles of decentralization, flexibility, participation and security.